Immune Profile Differences between IgG4-Related Diseases and Primary Sjögren’s Syndrome - Qin Y; Shang L; Wang Y; Feng M; Liang Z; Wang N; Gao C; Luo J (Journal of Inflammation Research)
Yan Qin,1 Lili Shang,2 Yanlin Wang,2 Min Feng,2 Zhaojun Liang,2 Nan Wang,2 Chong Gao,3 Jing Luo2 1Shanxi Center for Clinical Laboratory, Taiyuan, Shanxi, People’s Republic of China; 2Department of Rheumatology, The Second Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3Department of Pathology, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Jing Luo, Email ljty966@hotmail.comPurpose: Immunoglobulin G4-related disease (IgG4-RD) share clinical features with primary Sjögren’s syndrome (pSS). This study aimed to identify altered serological parameters and potential biomarkers of IgG4-RD and pSS.Methods: Forty IgG4-RD patients, 40 pSS patients, and 40 healthy controls (HC) were enrolled in this study. Routine serological parameters and clinical manifestations were assessed. IgG subclasses (IgGSc) were detected using a Siemens BN P, and lymphocyte subsets were analyzed using flow cytometry. Cytokines assays were performed using cytometric bead array.Results: Compared to pSS, IgG4-RD patients had higher IgG4 (p < 0.001) and lower IgG1 (p =0.014). The natural killer (NK) cells (p = 0.004), CD4+ T cells (p = 0.028), and TBNK cells (p = 0.040) were increased in IgG4-RD compared to pSS. IgG4 used to differentiate IgG4-RD from pSS produced an area under the curve (AUC) of up to 0.952. In addition, we compared serum parameters, immune cells, and cytokines of IgG4-RDwith mouth dryness or eye dryness with those of pSS with the same symptoms, and similar serological changes were observed. IgG4-RD patients with mouth dryness had higher IgG4 (p < 0.001) and Th cells (p = 0.016) but lower IgG1 (p = 0.009) compared to pSS with dry mouth. IgG4-RD patients with eye dryness had higher levels of IgG4 (p < 0.001), Treg cells (p = 0.037), and NK cells (p = 0.017) than pSS patients with eye dryness. Moreover, IgG4-RD patients with mouth and eye dryness had higher levels of B (p = 0.006), Th (p = 0.026), Th2 (p = 0.007), and Treg cells (p = 0.028) than IgG4-RD patients without mouth and eye dryness.Conclusion: Immune system disorder is an outstanding feature of IgG4-RD, and its feature differ from pSS. Assessment of immune status is important in the diagnosis and differential diagnosis of IgG4-RD.Keywords: IgG4-related disease, lymphocyte subsets, IgG subclasses, primary Sjögren’s syndrome, differential diagnosis